Recovery of the deep biosphere at the Chicxulub impact crater - Quraish, Sohaib Naseer (Curtin University, 2023)
This thesis employed molecular and geochemical analysis, revealing the diverse microbial communities involved in biogeochemical cycling that differed significantly between granite and non-granite rocks from the granitoid basement underlying the Chicxulub impact crater. These outcomes showed that in addition to newly formed lithologies, impact-induced geochemical boundaries within the crater still shape the recovered modern-day deep biosphere. This study provides a model system for searching for microbial life in the subsurface of well-preserved Mars impact craters.